Developing a green lending model for renewable energy project (case study electricity from biogas fuel at Palm Oil Industry). (March 2018) - Sukirman, Y A
Abstract: In the last two decades, development initiatives solely aimed to generate economic growth has been placed under scrutiny, particularly amidst the rampant discussion on the quality decline of the environment, growing social divide and climate change along with its implications thereof. Considerations of the negative impacts brought about by the economic development process prompted the move to adopt the sustainable financing model that gives precedence to economic, environmental and social aspects. We introduced Green Lending Model for Renewable Energy Project (Case Study Electricity From Biogas at Palm Oil Industry) based on sustainability financing, which is used as variable to implementing financial institutions' lending policies. There are two major trends in the literature relating to sustainability and the banking industry: external and internal practices. The external practices strand analyzes the relevance of sustainability to the bank's communication with shareholders and other stakeholders, and how investors use it as a measure to help achieve optimal portfolio allocation. The internal practices literature, more relevant to the present work, studies how sustainability criteria are integrated into risk management models and lending practices. Its first implementation is in the Palm Oil industry at South Sumatera. The results explained that sustainability is not related to profit either from a short- or long-term perspective. The Sustainable Green Lending Model is related to the Equator Principles and its application is driven to project financing. It also related with short- and long-term risks and opportunities, instead of short-term sustainability impacts.